The multiplicative decomposition method: Prediction of tuberculosis cases in Medan City - Fikry, Fikry Wira Afandi; Rima, Rima Aprilia (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to predict the number of Tuberculosis (TB) cases in Medan City for the year 2025, providing valuable information for healthcare workers and relevant stakeholders in their efforts to prevent and control TB infections. The research employs the Multiplicative Decomposition method, which divides time series data into four components: trend, seasonal, cyclical, and random. Utilizing TB case data from January 2020 to December 2024, obtained from the Medan City Health Department, the results indicate that the Multiplicative Decomposition method achieved a Mean Absolute Deviation value of 0.0376, a Mean Square Error value of 0.0549, and a Mean Absolute Percentage Error value of 0.00347%, demonstrating very good forecasting accuracy as all values are below 10%. The findings conclude that the Multiplicative Decomposition method is effective for estimating future TB cases, thereby supporting public health initiatives in Medan City.